POSSIBLE IMPACT OF THE EARTH'S MAGNETIC FIELD ON THE HISTORY OF ANCIENT CIVILIZATIONS - Gallet Y.; Goff M.Le.; Fluteau F.; Genevey A.; Eshraghi S.A. (My University, 2006)
We report new archeointensity results from Iranian and Syrian archeological excavations dated from the second millennium BC. These high-temperature magnetization data were obtained using a laboratory-built triaxial vibrating sample magnetometer. Together with our previously published archeointensity results from Mesopotamia, we constructed a rather detailed geomagnetic field intensity variation curve for this region from 3000 BC to 0 BC. Four potential geomagnetic events ("archeomagnetic jerks"), marked by strong intensity increases, are observed and appear to be synchronous with cooling episodes in the North Atlantic. This temporal coincidence strengthens the recent suggestion that the geomagnetic field influences climate change over multi-decadal time scales, possibly through the modulation of cosmic ray flux interacting with the atmosphere. Moreover, the cooling periods in the North Atlantic coincide with episodes of enhanced aridity in the Middle East, when abrupt societal changes occurred in the eastern Mediterranean and Mesopotamia. Although the coincidences discussed in this paper must be considered with caution, they lead to the possibility that the geomagnetic field impacted the history of ancient civilizations through climatically driven environmental changes, triggering economic, social and political instability. © 2006 Elsevier B.V. All rights reserved.
Keywords: ANCIENT CIVILIZATIONS; ARCHEOMAGNETISM; CLIMATE CHANGE; EASTERN MEDITERRANEAN; ENVIRONMENTAL IMPACT; MESOPOTAMIA